The neuromuscular, physiological, endocrine and perceptual responses to different training session orders in international female netball players - Birdsey, L. P.; Weston, M.; Russell, M.; Johnston, M.; Cook, C. J.; Kilduff, L. P. (European Journal of Sport Science, 2022)
The 20 h responses of International female netball players to training days requiring two sessions (netball and strength, separated by two hours) ordered alternatively were examined. Eleven players completed strength followed by netball training two hours later (STR-NET), with the order reversed (NET-STR) on a separate day. Well-being, neuromuscular performance (jump height [JH], peak power output [PPO], peak velocity [PV]) and endocrine function (testosterone, cortisol concentrations) were measured before sessions one (PreS1) and two (PreS2), immediately after sessions one (IPS1) and two (IPS2), and 20 h post session one (20P). Session and differential ratings of perceived exertion (upper-body, cognitive/technical [RPE-T], lower-body, breathlessness) were collected, and accelerometry and heart rate measured netball load. Identification of clear between-order differences was based on the nonoverlap of the 95% confidence interval (95%CI) for mean differences relative to baseline. Compared to PreS1, greater increases in JH (percentage difference between trials; 95%CI: 9%; 4-14%), PPO (5%; 2-8%), PV (3%; 1-5%) and cortisol concentration (45%; 1-88%), and a greater decrease for testosterone/cortisol ratio (-35%; -72 to -2%) occurred at PreS2 in NET-STR. At 20P, greater decreases in JH (10%; 5-15%), PPO (4%; 1-8%) and PV (4%; 2-6%) were observed following STR-NET. No differences existed for well-being, whilst RPE-T was greater (15 AU; 3-26 AU) for strength training during NET-STR. Session order influenced neuromuscular and endocrine responses in International female netball players, highlighting session ordering as a key consideration when planning training.